Understanding Multisided Platforms, Circular Economy and Tourism - Kunwar, Ramesh Raj (Journal of Tourism & Adventure, 2020)
A multisided platform is a model that creates value by facilitating exchanges between two transaction partners which means the platform plays an intermediary role between the two groups. This is also called “knowledge economy “or “third globalization” which has been brought into one platform through technology and information. In business, the platform is recognized as a marketing terminology. Comparatively the state, government, and civil society are influenced by various technologies in several fields of human activities and provide beneficiaries to human beings. This study aims to introduce the multisided platforms and their respective fields in businesses on one side and the other side, it shows the link between tourism and circular economy and explains why is circular economy becoming a key factor for contributing to keeping the balanced environment in highly industrialized, urbanized, overpopulation including over tourism. These days the circular economy has become closely associated with sustainability and sustainable tourism and development.